(3EYQGH GdbQBf GdcQje ddeHQO (B: s (3LeYG h OQGSI ebGQfI (B/ s - (3TQja eMeO YHOGdfHi EHQGgjes; (3ShRGf eMeO aDGO agei (B: s ((3GdbGgQI (B: s (3TQja eMeO YHOGdfHi EHQGgje (B: s, 2018)
(3bGe GdHMK HLeY EYQGH GdeHQO ddbQBf GdcQje ef cJHg h cJH ZjQg; HZQV LeYgG ai cJGH hGMO(B: (3h HjGf efgLg(B: (3h TNUjJg(B: (3h ehbag ef GdbQGAGJ GdbQBfjI(B: (3h HjGf Gdefbhd Yfg NWC(B: (3h Yed ebGQfI Hjfg hHjf KYdH Gdchai(B: (3dHjGf eOi GdGJaGb h GdGNJdGa Hjf GdHUQjjf h Gdchajjf ai EYQGH GdbQBf GdcQje(B: (3h bO LGA GdHMK HYfhGf EYQGH GdbQBf GdcQje ddeHQO LeYG h OQGSI ebGQfI h LGA ai ebOeI(B: (3h JegjO(B: (3h CQHYI aUhd Ydi GdfMh GdJGdi(B: (3GdebOeI(B: (3PcQJ ajgG CgejI GdehVhY(B: (3h CSHGH GNJjGQg(B: (3h HjGf efgLg h NWJg(B. (3GdJegjO(B: (3PcQJ ajg GdJYQja HGdeHQO(B: (3h GdJYQja HKYdH(B: (3h HjfJ Chd dbGA GdeHQO HKYdH(B: (3h JYQja (B((3GdEYQGH(B: (3GdbQBf(B: (3EYQGH GdbQBf GdcQje(B). (3GdaUd GdChd (B- (3GdBQGA GdGJaGbjI(B: (3PcQJ ajg GdBQGA GdGJaGbjI Hjf GdeHQO h KYdH(B: (3eQJHG h eMddG dgG(B. (3GdaUd GdKGfi (B- (3GdBQGA GdGNJdGajI(B: (3PcQJ ajgG GdBQGA GdGNJdGajI Hjf GdeHQO h KYdH(B: (3eQJHG h eMddG h eQLMG(B. (3GdaUd GdKGdK (B- (3GfaQGOGJ GdeHQO(B: (3PcQJ ajg eG fbd Yf GdeHQO ef EYQGHGJ ddbQBf GdcQje h de jfbd Yf KYdH(B. (3GdaUd GdQGHY(B- (3GdeHQO ef NdGd EYQGHg(B: (3ajg CQHYI eHGMK; GdeHMK GdChd (B- (3HjfJ ajg efgL GdeHQO ai EYQGHg ddbQBf GdcQje(B. (3GdeHMK GdKGfi (B- (3HjfJ ajg TNUjI GdeHQO GdfMhjI ef NdGd EYQGHg(B. (3GdeHMK GdKGdK (B- (3PcQJ ajg ehbag ef GdbQGAGJ GdbQBfjI(B. (3GdeHMK GdQGHY (B- (3NUUJg dHjGf Gdefbhd Yfg NWC(B. (3GdNGJeI (B- (3JMed Cge GdfJGFL GdJi NQL HgG GdHMK(B. (3GdagGQSs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdfMh h GdUQa h GdYQhVs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGJaGbjIs; (3GdGNJdGajIs; (3GfaQGOGJs